2019
DOI: 10.1016/j.jaac.2018.09.447
|View full text |Cite
|
Sign up to set email alerts
|

Parental Age and Differential Estimates of Risk for Neuropsychiatric Disorders: Findings From the Danish Birth Cohort

Abstract: Objective: Parental age at birth has been shown to affect the rates of a range of neurodevelopmental disorders, but the understanding of the mechanisms through which it mediates different outcomes is still lacking. We used a population-based cohort to assess differential effects of parental age on estimates of risk across pediatric-onset neuropsychiatric disorders: autism spectrum disorder (ASD), attention-deficit hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD) and Tourette syndrome/chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 73 publications
2
17
0
1
Order By: Relevance
“…Mikkelsen et al (2016) found in a population-based sample (N = 943,785) that offspring of mothers who gave birth to children early in their reproductive lives were more vulnerable to develop ADHD. This same outcome was also observed in a casecontrol (N = 10,409; N = 39,125) study by Chudal et al (2015) and in population-based cohort studies (N = 1,495,543; N = 1,490,745) by Chang et al (2014) and Janecka et al (2019). The results are more diverse for fathers; while Mikkelsen et al (2016) found no effect for fathers ' age, D'Onofrio et al (2014) reported in a population-based study (N = 2,615,081) that offspring of fathers 45 years and older were at higher risk for ADHD.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Mikkelsen et al (2016) found in a population-based sample (N = 943,785) that offspring of mothers who gave birth to children early in their reproductive lives were more vulnerable to develop ADHD. This same outcome was also observed in a casecontrol (N = 10,409; N = 39,125) study by Chudal et al (2015) and in population-based cohort studies (N = 1,495,543; N = 1,490,745) by Chang et al (2014) and Janecka et al (2019). The results are more diverse for fathers; while Mikkelsen et al (2016) found no effect for fathers ' age, D'Onofrio et al (2014) reported in a population-based study (N = 2,615,081) that offspring of fathers 45 years and older were at higher risk for ADHD.…”
supporting
confidence: 81%
“…Alternatively, SES could affect at what age offspring is born, which in turn influences offspring outcome. In that case, adjusting for SES could introduce bias (Janecka et al, 2019). Hence, we conclude that older parents tend to have offspring with fewer attention problems, higher IQ, and educational achievement, but for fathers the associations are small and mostly explained by higher SES.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We also observed significantly decreased MSEL scores when both parents were younger (under the age of 30). As noted, a number of studies have suggested that young parental age may also increase risk of adverse neurodevelopmental outcomes [Janecka et al, 2019;Lundstrom et al, 2010;Merikangas et al, 2017]. Liabilities associated with younger age at childbearing [Chen et al, 2008;Lundstrom et al, 2010] (see also below) may also influence risk of adverse cognitive development.…”
Section: Discussionmentioning
confidence: 95%
“…Beyond the well-documented associations with chromosomal disorders like Down syndrome, parental age has also been associated with other conditions with relevance to ASD [de Kluiver, Buizer-Voskamp, Dolan, & Boomsma, 2017;McGrath et al, 2014], though patterns of associations may differ. For example, studies have reported a nonlinear association between paternal age and offspring verbal IQ [Gajos & Beaver, 2017], increased risk of child intellectual disability with younger mothers [McGrath et al, 2014], and increased risk of attention deficit hyperactivity disorder and Tourette's/chronic tic disorder with younger parents [Janecka et al, 2019]. Prior work examining associations with quantitatively measured ASD-related traits is limited.…”
Section: Introductionmentioning
confidence: 99%